2020
DOI: 10.1039/d0ta05019a
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-alcohol@ZIF nanocomposites display suppressed phase-change temperatures

Abstract: The synthesis and characterization of phase change materials infused into metal–organic framework crystals to demonstrate high latent heats with suppressed phase change temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…For example, the decrease of the phase transition temperature of poly­(ethylene glycol) (PEG) has been observed when incorporated into graphene oxide, nanochannels of porous coordination polymers (PCPs), and carbonized MOFs . Recently, our group experimentally demonstrated the first encapsulation of SAs (erythritol and xylitol) within a class of MOF without an infusion process at room temperature . The nanoconfinement of the sugar alcohols was found to lower the melting point of the SAs into the operating range for water-cooling applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the decrease of the phase transition temperature of poly­(ethylene glycol) (PEG) has been observed when incorporated into graphene oxide, nanochannels of porous coordination polymers (PCPs), and carbonized MOFs . Recently, our group experimentally demonstrated the first encapsulation of SAs (erythritol and xylitol) within a class of MOF without an infusion process at room temperature . The nanoconfinement of the sugar alcohols was found to lower the melting point of the SAs into the operating range for water-cooling applications.…”
Section: Introductionmentioning
confidence: 99%
“…18 Recently, our group experimentally demonstrated the first encapsulation of SAs (erythritol and xylitol) within a class of MOF without an infusion process at room temperature. 19 The nanoconfinement of the sugar alcohols was found to lower the melting point of the SAs into the operating range for water cooling applications. However, the mechanism behind the observed melting point depression and the phase identification in the nanopores is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] The unique structure of MOFs enables them to exhibit excellent optical, electrical, magnetic, and photocatalytic properties, making them useful in energy conversion, storage, and transmission applications. [19] Xu et al [20] reported on an unprecedented nanocomposite PCM, which utilizes non-flammable, non-toxic, and high latent heat sugar alcohols encapsulated in an easily synthesized zeolitic imidazole framework (ZIF) crystals. The phase change temperature and latent heat of the composites were 19.8°C and 285 J/g, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Sugar alcohols possess large latent heat of melting, while experiencing a large degree of supercooling, which nominates them as good candidates for supercooling TES. For example, erythritol melts at ∼118 °C with a melting enthalpy of ∼340 J/g and mannitol at ∼167 °C with a melting enthalpy of ∼300 J/g. , However, they cannot operate reliably in a practical scale supercooling TES because spontaneous crystallization occurs in the supercooled state.…”
Section: Introductionmentioning
confidence: 99%